Description Of The Usage Of Antiretroviral Medicine With Atc/Ddd Method In The Primary Health Care Centers Of Kediri 2021 - Dandi Fathor Rozy Pradana Saputra; Chinthia Devientasari (Universitas STRADA Indonesia, 2024)
AIDS (Acquired Immune Deficiency Syndrome) is a collection of symptoms and infections caused by damage to the human immune system, HIV (Human Immunodeficiency Virus ), a virus that can weaken human immunity. PLWHA patients must undergo antiretroviral virus (ARV) drug therapy, one of the drug use analysis classification systems is using the ATC/DDD system which is a means of researching drug use in an effort to improve the quality of drug use, one of these components is the presentation and comparison of drug consumption levels. international. The aim of this research is to determine the use of antiretroviral drug consumption in primary health care center in the Kediri City area for the 2021 period using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method. The design of this research is quantitative descriptive, namely describing a particular event systematically and accurately and the treatment of this research is the process of collecting data and evaluating the use of antiretroviral drugs as well as verifying Primary health care center data by interviewing primary health care center pharmacists in the Kediri city area in 2021. Consumption of antiretroviral drugs (ARVs). ) is highest in the Campurejo primary health care center, namely Lamivudine (3TC) as much as 31.71%, Balowerti in primary health care center with Zidovudine (AZT) as much as 29.02% and Pesantren 1 primary health care center with the drug Nevirapine (NVP) as much as 32.62%, while the use of ARV drugs is low. At the Campurejo primary health care center, it was 0.0002% of the drug Dolutegravir (DTG), and at the Balowerti primary health care center, it was 0.0012% of the drug Dolutegravir (DTG), then at Pesantren 1 primary health care center , it was 0.0015% of the drug Dolutegravir (DTG). The incidence of HIV is still high in Indonesia, especially in the city of Kediri.